GAMBARAN KLINIKOPATOLOGI KARSINOMA PAYUDARA DI RSUP DR. M. DJAMIL PADANG TAHUN 2023 - Muhammad Rifki; Nana Liana; Irwan Triansyah; Roland Helmizar; Lismawati Lismawati; Desi Aliefia; Muhammad Rizki Saputra; Ruhsyahadati Ruhsyahadati; Rahma Triyana (Nusantara Hasana Journal, 2026)
Background: Breast cancer is a malignancy originating from epithelial cells of the breast ducts or lobules. Clinicopathological characteristics are important in determining prognosis and treatment. Understanding these features is essential to support early detection and improve management strategies. Objective: This study aimed to describe the clinicopathological features of breast cancer patients at RSUP Dr. M. Djamil Padang in 2023. Methods: This descriptive observational study used a cross-sectional design with secondary data. A total of 114 samples were collected using the total sampling technique. Data were analyzed using univariate analysis with Statistical Product and Service Solution (SPSS) version 25. Results: Among 114 breast cancer patients, the most common age group was 35–44 years, accounting for 37 patients (32.5%). The predominant histopathological subtype was Mixed Infiltrating Duct NST with Lobular Carcinoma in 37 patients (32.5%). Histopathological grading was most commonly grade 2 in 79 patients (69.3%). Positive lymphovascular invasion was identified in 76 patients (66.7%). The most frequent molecular subtype was Luminal B, found in 51 patients (44.7%). Conclusion: Breast cancer was most prevalent in patients aged 35–44 years. The dominant histopathological subtype was Mixed Infiltrating Duct NST with Lobular Carcinoma, with grade 2 and positive lymphovascular invasion most frequently observed. Luminal B was the predominant molecular subtype. Increasing awareness of early detection through breast self-examination is recommended.